Angkara Movie Based on Bali Traditional Art - I Komang Arba Wirawan; Paul Trinidad; I Dewa Made Darmawan; I Made Saryana; Made Rai Budaya Bumiarta; I Made Ruta (Mudra Jurnal Seni Budaya, 2023)
This research aimed to discover how the Angkara movie is based on Balinese traditional art and to find out the mise and scene in the pre-production, production, and post-production processes. Clekontong Mas for the Balinese people is a comedian studio (Bondres), which is well known and admired by the community. Clekontong is translated as ritual media, and Mas means noble. This studio was founded in Denpasar in 2012 and pioneered by I Komang Dedi Diana (Tompel), I Ketut Gede Rudita (Sokir), and I Nyoman Ardika (Sengap). Bondres  profoundly has the opportunity to be the inspiration for innovative film productions. However, there is no related research that has examined it further. The data sources used Angkara movies, film directors, cultural experts, and the audience. The method of data collection was conducted through observation, interviews, and documentation; online and offline. The Angkara movie was analyzed from the initial scene to the final scene qualitatively using the approach of setting, directing style, blocking, costumes, lighting, and revealing the aesthetics of the Angkara film. The result found that Angkara is a comedy genre film based on Balinese traditions. Directing style, and blocking the placement of Clekonteng Mas were successful role measurements in acting. The costumes of Angkara actors with traditional Balinese characteristics can describe the comedian's situation based on Balinese’s local wisdom. The social phenomenon in the production of the Angkara movie was produced and won national and international festivals. Presenting local Balinese cultural identity can be a source of film creation and characteristics to enrich the aesthetics of Balinese’s local wisdom in the form of films.